Investigation Of Diethylenetriamine-Tannic Acid (Deta-Ta) Coated Layer Onto The Membrane Surface For Separation Of Oil-In-Water Emulsions - Taupik, Mohamad Farhan Mohamad (Universiti Sains Malaysia, 2017)
In recent years the water pollution became a global concern due to the increasing of the waste oil generation. This phenomenon was exacerbated by the expansion of industrial activities due to the increasing in the amount of oil used in this industries. Many efforts were conducted to reduce the level concentration of oil from the industrial effluents. Membrane filtration system was proposed as an alternative technique to overcome disadvantages of the conventional oily wastewater treatment. However, there are still many challenges in order to commercialize the membrane filtration such as membrane surface stability, oil rejection efficiency and compatibility between coating solution and membrane material. In order to solve this problem, a hydrophilic coated layer of Diethylenetriamine/Tannic Acid (DETA/TA) had been coated on the outer surface of the Polyvinylidene Fluoride (PVDF) membrane via polyphenolic coating method. Parameters to prepare hydrophilic surface (mass ratio of DETA/TA, concentration of Tannic Acid (TA), pH of coating solution and coating time) had been studied and optimized. It was observed that the DETA/TA ratio of 2:1 did produce polymeric surface with lower water contact angle (WCA). The increasing of TA content in the coating solution up to 5 g/L led to the decreased of WCA from 39.5° to 19.4°. The hydrophilicity of the coated layers were analysed in terms of surface roughness, physical structure and water contact angle. It was found that the WCA of the coated PVDF membranes surfaces prepared via polyphenolic coating were less than the native surface. A cross flow filtration system was designed to evaluate the antifouling performance of modified membranes in term of oil removal. The operating parameter which is Transmembrane Pressure (TMP) on the oil removal were studied. The antifouling performance was investigated for native and modified membrane. However both membranes not showed with good antifouling property. In addition, it was observed that the modified PVDF membrane had higher oil rejection than unmodified ones at the same feed concentrations and operating conditions.